2018
DOI: 10.1111/jocn.14297
|View full text |Cite
|
Sign up to set email alerts
|

Re‐embodying eating after surgery for oesophageal cancer: Patients' lived experiences of participating in an education and counselling nutritional intervention

Abstract: There is a need for systematic long-term follow-up after surgery for oesophageal cancer regarding nutrition. The findings of this study can inform future supportive nutrition care service development aimed at supporting patients to learn to eat sufficiently after oesophageal resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…A diagnosis of GI cancer may have a large impact on a person's lifestyle, and especially on diet. Difficulties in food ingestion/digestion following surgical treatment or routine chemo/radio therapies, as well as food restrictions, specifically in patients with esophagus and gastric cancers, lead to the possibility of an undesired diet quality among GI cancer survivors [2,3]. It is also known that a healthy diet will improve outcomes after a diagnosis of GI cancer [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A diagnosis of GI cancer may have a large impact on a person's lifestyle, and especially on diet. Difficulties in food ingestion/digestion following surgical treatment or routine chemo/radio therapies, as well as food restrictions, specifically in patients with esophagus and gastric cancers, lead to the possibility of an undesired diet quality among GI cancer survivors [2,3]. It is also known that a healthy diet will improve outcomes after a diagnosis of GI cancer [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence indicates a need among GI cancer survivors for information on diet and nutrition to improve diet quality [3]. Nonetheless, related investigations yield inconsistent findings; while some studies demonstrate improved dietary awareness [5], or a stable adherence to healthy diets [6], other studies demonstrated a poor diet quality status in cancer survivors [2,3,7]. This inconsistency might be partly due to the variety of study populations and the associated cancer types, cultural differences, variation in time since diagnosis, inconsistent methods of dietary assessment, or methods of dietary assessments which are not in accordance with evidence-based dietary guidelines [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, patient experiences in the current study stress the need for interventions enabling nursing staff to have education about nutrition and how to provide individual counselling and care about nutrition to patients during hospitalisation. Structured nutritional counselling has previously been integrated with other clinical settings and seems to support self‐management skills (Missel, Hansen, Jackson, Siemsen, & Schønau, ).…”
Section: Critical Interpretation and Discussionmentioning
confidence: 99%
“…The authors found that nurses in general considered nutrition important, however, when the nurses ranked providing nutrition care (like serving meals rich in proteins and calories), they found it a less important task (Boaz et al, 2013). Other clinical settings and seems to support self-management skills (Missel, Hansen, Jackson, Siemsen, & Schønau, 2018).…”
Section: Most Of the Patients Had No Experience Of Receiving Nutritionalmentioning
confidence: 99%
“…It has been well described that patients are in need of help to recount and understand their illness experiences (Aho, 2018; Kleinman, 1988; Rose, 2007). A life afflicted with severe illness is likely to be sweepingly changed, leading to demanding existential efforts that require comprehensive support (Beck et al, 2017; Missel et al, 2018; Simonÿ et al, 2017). The research underlines that it is important that nurses and other healthcare professionals engage with the patients’ lived experiences and recognize the importance of these experiences concerning the personal recovery process (Davidson, 2016; Karlsson, 2009; Slade et al, 2014).…”
Section: Introductionmentioning
confidence: 99%